An Evaluation of Telepractice During the COVID-19 Pandemic for the Treatment of Speech and Language Disorders in Belgium - Ronny Boey; Stefaan Lefevere (International Journal of Telerehabilitation)
The aim of this article was to evaluate the sudden implementation of telepractice in Belgium during the COVID-19 pandemic. A 38-question survey was completed by 1,222 Dutch-speaking speech-language pathologists (SLPs) from Belgium. Most reported good or very good satisfaction with telepractice and that telepractice can be effectively used with clients of different ages and speech disorders with or without comorbidity. The SLPs reported when telepractice could be used most effectively. They also detailed their difficulties with both technology and client-related issues. Limitations when switching to telepractice included a lack of training and experience, and digital materials.